Systematic experimental study of quantum interference effects in anthraquinoid molecular wires - Carlotti, Marco; Soni, Saurabh; Qiu, Xinkai; Sauter, Eric; Zharnikov, Michael; Chiechi, Ryan C. (Nanoscale advances, 2019)
In order to translate molecular properties in molecular-electronic devices, it is necessary to create design principles that can be used to achieve better structure-function control oriented toward device fabrication. In molecular tunneling junctions, cross-conjugation tends to give rise to destructive quantum interference effects that can be tuned by changing the electronic properties of the molecules. We performed a systematic study of the tunneling charge-transport properties of a series of compounds characterized by an identical cross-conjugated anthraquinoid molecular skeleton but bearing different substituents at the 9 and 10 positions that affect the energies and localization of their frontier orbitals. We compared the experimental results across three different experimental platforms in both single-molecule and large-area junctions and found a general agreement. Combined with theoretical models, these results separate the intrinsic properties of the molecules from platform-specific effects. This work is a step towards explicit synthetic control over tunneling charge transport targeted at specific functionality in (proto-)devices.
Gesehen am 14.04.2020